Newborn ankyloglossia and breastfeeding - Zlata Felc; Danijel Žerdoner (Zdravniški Vestnik, 2007)
Background: Tongue-tie (ankyloglossia) is a relatively common finding in the newborn population and represents a significant proportion of breastfeeding problems. Ankyloglossia may result in difficulty with suckling and can lead to poor weight gain, sore nipples, low milk supply, maternal fatigue and frustration. Conclusions: By recognizing ankyloglossia early, the health care team is able to treat breastfeeding problems promptly and proactively. The pediatrician, oral-maxillofacial surgeon, and parents should work together as a team from the time of birth to determine a coordinated plan of treatment. Careful assessment of lingual function is important in selecting the correct treatment. Frenulotomy is indicated in newborns with a short and/or thick frenulum and limited lingual mobility. In newborn infants with ankyloglossia this minimal surgical procedure is an effective therapy for breastfeeding difficulties.